Flora das cangas da Serra dos Carajás, Pará, Brasil: Celastraceae - Lombardi, Julio Antonio [UNESP] (2016)
This study presents the species of Celastraceae registered for the cangas of Serra dos Carajás, Pará state, including morphologic descriptions, illustrations, and comments. Four species were found in the region: Anthodon decussatum, liana widely distributed in the Neotropics; Cheiloclinium hippocrateoides, liana restricted to Amazon basin; Maytenus guyanensis, shrub or tree widely distributed in the Neotropics; and Tontelea laxiflora, liana occurring in the Amazon basin and northeastern Brazil.